Effects of plyometric training and resistance training in adolescents basketball players - Vila Dos Santos, F.; Bassan, J. C.; Szkudlarek, A. C.; Zapani, A. K. M.; Camilo, E.; Souza, R. F.; Santos, J. A. H. (Archivos de medicina del deporte, 2008)
The acquirement of force in inferior members has showed to be an available and representative element for the increases of performance in basketball athletes with the objective to seek improvements in the motion speed and jumps. The aim of this study was to examine in 16 teenagers male basketball players (mean age 16) the most efficient methodology to gain explosive power and strength (plyometric or resistance training) to improve vertical jump (VJ), horizontal jump (HJ) and the speed racing (V) performances. This research was approved by the Human research Ethics Committee of Dom Bosco`s College. The subjects were divided in 2 groups. The plyometric group (PG) made plyometrics exercises two times a week, forty fi ve minutes each for three months. The athletes made several types of progressive plyometric jumps. The Resistance Force Group (RFG) trained resistance two times a week, fi fty minutes each for three months using muscle equipments and free weights (3 series of 15 to 20 repetitions each, loads o 60 to 70% of 1RM test). The muscle groups worked were quadriceps, hamstring and gastrocnemius. To verify the efficacy of the applied methodologies were made the long jump test, the sergeant test and the 30 meters test. The training and the testing procedures were tolerated by the subjects. The results showed that the plyometric training brought significant increases in the HJ performance (first -test: 195 ± 0,18 cm and last-test: 218 ± 0,14 cm ; p<0,05) and in the VJ performance (fi rst -test: 45,75 ± 6,11 cm and last-test: 51,50 ± 6,74 cm; p<0,05). However, no signifi cant improvement was found in the V performance provided by plyometric training (first -test: 4.76 ± 0.15 sec and last-test: 4.72 ± 0.18 sec). The RFG did not show signifi cant improvements in any of the variables. Besides, it was observed that the RFG had a significant decrease in the V test performance (first -test: 4.55 ± 0.26 sec and last-test: 4.82 ± 0.36 sec; p<0,05). These results suggest that improving strength and explosive force to increase the HJ and VJ performance should be performed by plyometric exercises because they are specific to basketball game movements. We speculate that the resistance training should be worked with other forms of training like jumps and velocity exercises.